The effect of screw angulation and insertion torque on the push-out strength of polyaxial locking screws and the single cycle to failure in bending of polyaxial locking plates - Bufkin, B. W.; Barnhart, M. D.; Kazanovicz, A. J.; Naber, S. J.; Kennedy, S. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
Objective: To evaluate the mechanical properties of the Polyaxial Advanced Locking System (PAX) in screw push-out and four-point bending.Materials and methods: Screw push-out: PAX locking screws were applied to first generation PAX plates at three different insertion angles with two different insertion torques. A load was applied parallel to the screw axis, and screw push-out force was measured. Four-point bending: PAX plates were applied to a bone model and a fracture gap was simulated. Bending stiffness, bending strength, and bending structural stiffness were evaluated and compared to published data.Results: Screw push-out forces were significantly higher at 0 and 5 degree insertion angles when compared with an insertion angle of 10 degrees. An insertion torque of 3.5 Nm also produced significantly higher push-out forces compared to 2.5 Nm. Four-point bending: Qualitative comparison of the data gained in this study with previously published data suggests that the PAX system bending stiffness and bending structural stiffness seems to be higher than that of other veterinary orthopaedic implants, but the bending strength was similar.Clinical relevance: The PAX locking system offers the benefit of polyaxial screw insertion while maintaining comparable biomechanical properties to other currently available orthopaedic implants.
Keywords: locking screws; locking plates; bone plate; Polyaxial; push-out strength; insertion torque; screw angulation